2012
DOI: 10.1007/s00436-011-2798-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Trichomonas vaginalis activity of saponins from Quillaja, Passiflora, and Ilex species

Abstract: Trichomonas vaginalis is a flagellated protozoan that causes trichomonosis, the most prevalent non-viral STD worldwide. The pathogen has been associated with serious health consequences including predisposition to cervical cancer and adverse pregnancy outcomes and infertility. It also acts as a co-factor in HIV transmission and acquisition. The 5-nitroimidazole drugs are used in the treatment, however, treatment noncompliance is observed, and a growing number of T. vaginalis isolates resistant to the drugs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…P. lentiscus 15 mg/ml and O. bacilicum oil 30 lg/ml showed statistically significant difference when compared to metronidazole 20 lg/ml after 24 h incubation. These findings were in accordance with the results of Ali (2007) who reported similar inhibitory effect when using Propolis, and also those of Rocha et al (2012) when using saponins from Quillaja, Passiflora and Ilex species on the axenic culture of T. vaginalis. The similarity between the effects of natural products in this study and other studies on T. vaginalis trophozoites can be attributed to the possibility that different plants may share the same active ingredients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…P. lentiscus 15 mg/ml and O. bacilicum oil 30 lg/ml showed statistically significant difference when compared to metronidazole 20 lg/ml after 24 h incubation. These findings were in accordance with the results of Ali (2007) who reported similar inhibitory effect when using Propolis, and also those of Rocha et al (2012) when using saponins from Quillaja, Passiflora and Ilex species on the axenic culture of T. vaginalis. The similarity between the effects of natural products in this study and other studies on T. vaginalis trophozoites can be attributed to the possibility that different plants may share the same active ingredients.…”
Section: Discussionsupporting
confidence: 82%
“…In general, isolated plant's substances such as flavonoids, alkaloids, cumarins, saponins and glycosides have demonstrated activity against different flagellates such as G. lamblia (Barbosa et al 2007), Trichomonas gallinae (Adebajo et al 2006), T. vaginalis (Arthan et al 2008), and Leishmania infantum (González-Coloma et al 2011). Anti-T. vaginalis activity of other plant's saponins was reported (Rocha et al 2012). Thus, the anti T. vaginalis activity reported in this study can be attributed to the saponin content of O. bacilicum oil as well as the biologically active flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts (Frasson et al, 2012), essential oils (Moon et al, 2006), and isolated substances such as saponins (Rocha et al, 2012), b-glycosides (Arthan et al, 2008), and alkaloids (Giordani et al, 2011) have shown anti-T. vaginalis activity, but until now, no study on the action of A. tsao-ko essential oil and geraniol against T. vaginalis or other protozoa is available. In this study, the anti-T. vaginalis activity of A. tsao-ko essential oil and geraniol against two isolates of T. vaginalis was investigated, showing obvious anti-T. vaginalis activity.…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole and tinidazole were the two drugs of choice recommended by the United States Food and Drug Administration for the treatment of this STD (Helms et al, 2008). Although the cure rate was high, these drugs demonstrated treatment failure which was normally related to non-compliance because of side effects such as headache, dry mouth, metallic taste, glossitis, and urticaria caused by lengthy treatment or high doses (Garduño-Espinosa et al, 1992;Kapoor et al, 1999;Oxberry et al, 1994), or reinfection (Rocha et al, 2012). Moreover, an increasing number of metronidazole-resistant T. vaginalis isolates have been reported since metronidazole was introduced for the treatment of trichomoniasis in 1959 (Blaha et al, 2006;Butler et al, 2010;Durel et al, 1967;Narcisi & Secor, 1996;Schmid et al, 2001; Upcroft et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that in combination with PNS, the dose of cisplatin could be reduced without affecting the tumoricidal efficiency leading to reduction in side effects. Other saponins such as those isolated from Passiflora alata and Quillaja saponaria exhibited strong anti-Trichomonas vaginalis activity (Rocha et al, 2012). It is noteworthy that T. vaginalis, a flagellated protozoan that causes trichomonosis, is knowm to be associated with serious health consequences including pelvic inflammatory disease, predisposition to cervical cancer, etc (Petrin et al, 1998).…”
Section: Mechanismsmentioning
confidence: 99%